Assessment of Nutrient Intake and Anthropometric Indicators among Elderly Individuals in Sukinda Block, Odisha (International Journal of Food and Nutritional Sciences, 2026)
The present study aimed to assess the nutrient intake, nutritional status, and dietary gaps among the elderly population of Sukinda block in Jajpur district, Odisha. A descriptive cross-sectional research design was adopted, and 75 elderly individuals aged 55 years and above were selected using purposive sampling. Data were collected through a semi-structured interview schedule that included socio-demographic details, dietary assessment using 24-hour recall and food frequency questionnaire, and anthropometric measurements such as height, weight, body mass index (BMI), mid-upper arm circumference (MUAC), and calf circumference. The findings revealed that the mean intake of energy, protein, calcium, iron, and essential vitamins was below the recommended dietary allowances (RDA), indicating significant dietary inadequacies. Anthropometric assessment showed the coexistence of undernutrition and overweight, reflecting a dual burden of malnutrition. A considerable proportion of participants exhibited low MUAC values and were at risk of chronic diseases such as diabetes and osteoarthritis. Socioeconomic dependency, limited dietary diversity, poor awareness regarding balanced diets, and age-related physiological changes were identified as major contributing factors. The study highlights the urgent need for targeted nutritional interventions, strengthened geriatric healthcare services, and community-based awareness programs to improve dietary practices and promote healthy aging among the elderly population.